Enhanced Photocatalytic Activity of Au/TiO2 Nanocomposite Prepared Using Bifunctional Bridging Linker. (9th September 2013) - Miljevic, Marko; Geiseler, Bianca; Bergfeldt, Thomas; Bockstaller, Pascal; Fruk, Ljiljana
<x xml:space="preserve">Abstract</x> Using a simple bifunctional bridging linker, nanosized gold and titanium dioxide composites are prepared containing different Au loadings. Linker is synthesized to contain both catechol and thiol moieties to enable binding to the TiO2 and Au surface respectively. Au/TiO2 nanocomposites are prepared using simple synthetic route that allows the control over the amount of Au nanoparticles, a property which plays a significant role in the catalytic activity of hybrid materials. Photocatalytic activity of materials prepared using different TiO2 precursors is investigated using reactive oxygen species sensitive assay based on activation of horseradish peroxidase (HRP) enzyme. Significant increase in catalytic activity is observed for all Au/TiO2 nanocomposites with Au/TiO2 prepared by use of the bridging linker being up to 5.5 times more active than bare commercial TiO2 nanoparticles. In addition to 365 nm light excitation, less energetic 470 nm light, which is more suitable for the use with biological systems, is used to induce photocatalytic activity. Finally, prepared photocatalytic materials are successfully used to exert temporal control over enzymatic activity, a feature which is important for the study of both enzymatic activity and design of novel bio‐sensing platforms.